Determinants of Relative Sectoral Prices: The Role of Demographic Change1. (30th November 2016) - Groneck, Max; Kaufmann, Christoph
Abstract: Demographic change raises demand for non‐tradable old‐age related services relative to tradable commodities. This demand shift increases the relative price of non‐tradables and thereby causes real exchange rates to appreciate. We claim that the change in demand affects prices via imperfect intersectoral factor mobility. Using a sample of 15 OECD countries, we estimate a robust increase of relative prices. According to our main estimate, up to one fifth of the average increase in relative prices between 1970 and 2009 can be attributed to population ageing. Further findings confirm the relevance of imperfect factor mobility: Countries with more rigid labour markets experience stronger price effects.